Ifatinuké entre-lugares, embarques e desembarques em costas brasileiras e africanas: um estudo sobre representação indenitária na religião de matriz iorubá/nagô, em Pernambuco. - Lima, Claudia Maria de Assis Rocha (2019)
This thesis had as objective investigate from the Pernambucan Xangô´s identity representation to the an Ifatinuké´s confiscated history, the African funder of the Recife´s Yoruba/ Nagô first house and the title owner of the property, in which functionate until present, with the denomination of Sítio de Pai Adão. In this process was observed the dissonance of oral narratives and ethnographic records from the 30´s, in which Ifatinuké, Tia Inês stands out as an established origin ´´myth´´, removing the pioneering and protagonism of the real maintainer of Ogunté´s Terreiro and the ancestral rights of their memories. Therefore, starting from bibliographic references and between the lines of the ´´unspoken´´, the methodology that took account of analyzing, comparing and coordinate the resulting data of this research was the Carlo Ginzurg´s indicial paradigm. The indicial paradigm implies in examinate the most neglected details, proposing with this method dozens and dozens of new perspectives, in which brought to visibility the Ifatinuké´s time line, diluted in forgetfulness, throughout the documental records, certificates, journals, having Clã Adamita as the articulator of speech of being the Babalorixá, Felippe Sabino da Costa (Pai Adão), the original Ogunté´s Terreiro founder. The technic-conceptual route was stablished based on Roger Chartier stablishing a dialog with diverse thinkers that functioned in an integrated way, revealing traces of the religious fabric and it peripheric nuances. The conceptual focus initially happens around the representation that according to Chartier, are not neutral speeches: they produce strategy and tendent practices to impose an authority, a deference and even to legitimate choices. Highlighting that these are placed in the field of competition and contention. This study was not restricted to the historiographic narrative about the coming and going between Atlantic shores, but in the observance that such inter-places performances (Homi Bhabha) of theses historical individuals were imperious for the composition of the identity representation of the set of characteristics that define the Yoruba/Nagô ethnic group in Brazil. In order to work onexa the nuances of a presumed trajectory of Tia Inês, transatlantic traveling priests were listed, their traces and vestiges being (re)constructed and (re)signified from the bibliographic records, interspersed by orality, focusing on the transit to Pernambuco, ate the crossing between Lagos, Rio de Janeiro, Bahia, Pernambuco and vice-versa, seeing among these figures common points that referred back to the founder of Pernambuco´s Yoruba/Nagô first house, the freed African Ifatinuké, Ignes Joaquina da Costa, better known as Tia Inês. In this context, attributing that place legal and religious right of the ancestral memory of Ifatunuké before the historiographical affirmations in the year of her centenary of death (1919 – 2019).